LED-supplied blue light mitigates ammonium toxicity in rapeseed (Brassica napus L.) - Li, Wenjing; Song, Jinnan; Sun, Qingbing; Yang, Jingli; Zhang, Jingmin; Xu, Haicheng; Peng, Dianliang; Sang, Maopeng; Jeong, Byoung Ryong (Frontiers in Plant Science, 2025)
Ammonium (NH4+) toxicity adversely curtails the growth and productivity of rapeseed plants. Current knowledge shows that blue (B) light is an alternative approach used to minimize or alleviate disturbances caused by various abiotic stresses. However, few studies have investigated NH4+-stressed rapeseed plants to illustrate the alleviatory role of blue light. Therefore, this study was conducted to determine whether blue light could reduce the degree of NH4+ toxicity in rapeseed and, at the same time, elucidate the underlying mechanism. To this end, rapeseed plants were cultured in a controlled environment (14 h light at 22°C and 10 h dark at 18°C) and treated with one of three NH4+:NO3− regimes (0:100, 50:50, and 100:0) with a constant nitrogen concentration of 13 me L−1, under white light-emitting diode (LED) light or blue LED light at 200 PPFD. Plants treated exclusively with NH4+ under white light exhibited decreased growth, disturbed photosynthesis, inhibited antioxidant defense systems, limited nitrogen (N) assimilation, and ultimately developed NH4+ toxicity symptoms (as characterized by chlorosis, necrosis, and stunted morphology). These traits and parameters were significantly mitigated by blue light treatment. Collectively, this study highlights the benefits of blue light on plants, particularly for NH4+-sensitive species such as rapeseed.